1990
DOI: 10.1111/j.1751-1097.1990.tb01810.x
|View full text |Cite
|
Sign up to set email alerts
|

TRANSIENTS OF URACIL and THYMINE DERIVATIVES and THE QUANTUM YIELDS OF ELECTRON EJECTION and INTERSYSTEM CROSSING UPON 20 ns PHOTOLYSIS AT 248 nm

Abstract: Transients of uracil and a series of 17 correlated pyrimidines, e.g. methylated bases, nucleosides, nucleotides, and polyuridylic acid [poly(U)] were studied after 248 nm excitation by 20 ns laser pulses. The transient absorption spectra in aqueous solution at room temperature reveal the triplet state and the hydrated electron (e-aq), while the corresponding radical cation could not be observed at pH 6-7. Fast loss of the chromophore in the 260-290 nm range within 0.1 microsecond was observed in aqueous soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 45 publications
4
38
0
Order By: Relevance
“…Understanding these pathways would assist in predicting how low‐intensity UV radiation damages DNA and RNA in living organisms. Monophotonic ionization of DNA bases has been confirmed experimentally for 193 nm laser pulses in aqueous solution (7–11).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Understanding these pathways would assist in predicting how low‐intensity UV radiation damages DNA and RNA in living organisms. Monophotonic ionization of DNA bases has been confirmed experimentally for 193 nm laser pulses in aqueous solution (7–11).…”
Section: Introductionmentioning
confidence: 91%
“…We also investigated the effect of the substituent at pyrimidine N1 and purine N9 on PI. Substituents have been found to affect the photophysical and photochemical properties of the DNA bases (8,19–21). The lifetimes of electron and triplet states, the relative yields of triplet formation and the quantum yields of hydrated electrons of some uracil and thymine (Thy) derivatives in aqueous and organic solutions are dependent on the substituents and on their position of attachment (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the initial linear increase of Qe-vs intensity (at low values) it has been concluded that the electrons and respective base radical cations are produced by consecutive biphotonic excitation Opitz and SchulteFrohlinde, 1987;Wala et al, 1990;Gorner, 1990a). Also for RNA and DNA Nikogosyan (1990) and his group have shown that Qe-increases with increasing ps laser pulse intensities and reaches a maximum.…”
Section: Photoionizationmentioning
confidence: 99%
“…Some values for GC-of nucleic acids are compiled in Table 1. The absorption of the resulting radical cations has not yet been observed with nucleic acids and their constituents since either the extinction coefficients are too low or the lifetimes of the radical cations under those conditions are too short (Wala et at., 1990;Bothe et al, 1990;Gorner, 1990a).…”
Section: Photoionizationmentioning
confidence: 99%